Legal Harmonization and Implementation Challenges of the ASEAN Agreement on Electronic Commerce: A Comparative Study of Indonesia and Malaysia - Aprila Niravita; Ayup Suran Ningsih; Hazlina Binti Shaik MD Noor Alam; Faizin Sulistio; Harumsari Puspa Wardhani (International Law Discourse in Southeast Asia, 2026)
The rapid growth of e-commerce in Southeast Asia has intensified the need for a harmonized legal framework to ensure legal certainty, protect consumers, and facilitate cross-border digital trade. This issue is closely aligned with Sustainable Development Goal (SDG) 8 on promoting sustainable economic growth through digital trade and SDG 16 on strengthening effective legal institutions and access to justice, while also supporting digital innovation under SDG 9. In response, ASEAN adopted the ASEAN Agreement on Electronic Commerce (AAEC) as a regional instrument to advance digital economic integration among its member states. This study examines the harmonization and implementation of AAEC provisions in Indonesia and Malaysia and identifies the challenges affecting their effective application. Employing a comparative juridical approach, the research analyzes national regulations governing electronic commerce and digital trade, supported by policy documents, official reports, and relevant empirical studies. The novelty of this research lies in evaluating both the conformity of domestic regulations with AAEC provisions and the practical implementation challenges influencing regional legal harmonization. The findings demonstrate that both countries have incorporated the core principles of the AAEC into their domestic legal frameworks, particularly regarding recognition of electronic transactions, consumer protection, and personal data governance. Nevertheless, substantial differences remain in regulatory readiness, institutional coordination, enforcement capacity, digital infrastructure, and the preparedness of micro, small, and medium enterprises (MSMEs). Malaysia exhibits stronger institutional readiness and regulatory consistency, whereas Indonesia continues to face regulatory fragmentation and uneven implementation across sectors. The study concludes that effective AAEC implementation depends not only on harmonized legal norms but also on robust institutions, coordinated enforcement, and inclusive digital capacity-building. These findings contribute to the development of regional digital trade governance by providing policy recommendations to strengthen legal harmonization, institutional cooperation, and digital inclusion, thereby supporting ASEAN's digital economic integration.